Pemberdayaan Masyarakat Sebagai Upaya Pencegahan Demam Berdarah Dengue Di Desa Gheoghoma - Tokan, Pius Kopong; Owa, Krispina (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2023)
Dengue Haemorrhagic Fever (DHF) apart from causing public health problems, is also a fairly high economic burden. The number of cases is increasing and the spread is getting wider, especially in areas where the temperature and humidity conditions allow the Aedes spp vector to live. Facing this problem, one solution that can be developed is empowering the community through the 1R1J movement which aims to increase ABJ DHF in the village of Gheoghoma, North Ende District, Ende Regency. Research method: this type of quantitative research, the design of the same group is given two different treatments, namely pre-intervention-post. The research was spread across three hamlets in the village of Gheoghoma during February-April 2023. Population.The study consisted of 200 households (RT) and selected 150 RTs as samples obtained by probability method, simple random sampling technique, and fulfilled the inclusion criteria. Data were collected by observing larvae and then recorded in the provided format. Data processing begins with the process of editing, coding, tabulating, checking the final data, then calculating ABJ. Then the normality test was carried out and continued with Wilcoxon test Result: ABJ before intervention was 35.33%, and after the intervention was 84.7% (an increase of 49.37%). After the normality test was interpreted the data were not normally distributed with asymp values. Sig. (2-tailed) is 0.000, less than a 0.05. Conclusion: community empowerment through the 1R1J movement can increase DHF ABJ in the village of Gheoghoma, Ende Utara District. Suggestion: Jumantik homes are trained to become role models while inviting other families to participate in the 1R1J movement so that they need to get support from both village stakeholders and the technical sector, namely the Health Service and Puskesmas. In addition, research is needed to develop new ideas and innovations